Diverging Paradigms of Citizenship: A Comparative Content Analysis of Elementary Civic Education Textbooks in Indonesia and Thailand - Aina Nurdiyanti; Iis Husnul Hotimah; Molraphaporn Boontrac; Muhammad David (Actual Insight, 2026)
Civic Education at the elementary level plays a strategic role in shaping students’ character, civic awareness, and democratic competence, while textbooks as primary learning resources strongly influence how civic values are framed, understood, and practiced. This study is novel in providing one of the first systematic, cross-national comparative analyses of Indonesian and Thai elementary Civic Education textbooks, integrating textbook content analysis with teacher perspectives to reveal divergent civic paradigms in Southeast Asia. Employing a qualitative descriptive design with a comparative content analysis approach, six officially approved textbooks were examined using an analytic matrix encompassing curriculum alignment, language readability, appropriateness of illustrations, and representation of civic values; these findings were triangulated with thematic analysis of responses from 25 Indonesian elementary teachers. The results indicate that Indonesian textbooks demonstrate relatively strong curriculum alignment, employ communicative language and contextual illustrations, and integrate Pancasila-based values through everyday narratives, although conceptual depth remains uneven across grade levels and often requires teacher adaptation. In contrast, Thai textbooks emphasize social harmony, loyalty, and national identity through more formal language and limited visual scaffolding. Overall, the findings reveal contrasting paradigms in textbook design: Indonesia is moving toward student-centered, competency-oriented civic learning, whereas Thailand remains largely normative and state-centered. The implications underscore the need for more consistent conceptual depth, multimodal resources, and structured opportunities for critical engagement so that Civic Education textbooks become more contextual, inclusive, and pedagogically robust in supporting contemporary goals of democratic citizenship education.